Impact of Grazing on the Plant Composition and Dominance of Natural Grassland and Established Silvipasture - Rai, P (Annals of Arid Zone, 2025)
TIle impact of grazing on plant composition and dominance of natural grassland, as well as plant population of established silvipasture, were studied at Jhansi from October 1991 to June 1994. There was no harmful effect on the plant composition and dominance of the perClUlialgrasses in natural grassland due to round year grazing. Similarly, plant population of Chrysopogoll fulvus was also not aITected due to round Ole year grazing by sheep and goats under silvipastoral system. However, legume components drastically decreased under natural grassland, as well as in silvipastoral system. Out of Orreetree species, Leucaella leucocepJwla survived minimum (11.5%), followed by Dichrostachys cillerea (64.0%) under grazing conditions. Thus, it can be concluded Olat the legume components are affected’ severely by grazing in both Ole types of pasture eVClIWiOIoptllmun stocking rate of anllnals. In tree species, L. leucocephala was also affected adversely, while pereIUlial grasses did not show any harmful effect of grazing.